Pengembangan Sistem Suplai Brown Gas Model 6 Ruang Tersusun pada Mesin Mobil 1300cc dengan Sistem Karburator - Harus Laksana Guntur; Rasiawan .; B. Sampurno; I Nyoman Sutantra (Jurnal Teknik Mesin (Sinta 3), 2011)
Brown gas, known as H2O2 (Oxyhydrogen) obtained from electrolysis process can be mixed with gasoline and used in the internal combustion engines. Uncontrolled mixing of Brown gas in the internal combustion engines reduces the quality of burning (engine performance). In this paper, the development and application of the Brown gas generator with 6 chambers in series-equipped with controller is reported. The gas production rate was controlled by regulating the supply current using Pulse Width Modulation (PWM). The characteristic of the Brown gas supply system was tested for various concentrations of the catalyst (KOH) and temperatures. The Brown gas supply system was then applied to the carburetor type engine of 1300 cc and the engine performance was tested. The test results show that the maximum production of gas occurred at 30% of catalyst (KOH) and the production of gas is proportional to the room temperature. The engine performance test result show a 30% reduction of specific fuel consumption after installation of the Brown gas supply system to the engine. The emission test results show 0.67% to 0.12% reduction of CO and 16.9% to 15.5% reduction of CO2.